Monitoring the cerebral venous drainage in space missions: the Drain Brain experiments of the Italian Space Agency - Silvia Mari; Anselmo Pagani; Giovanni Valentini; Gabriele Mascetti; Salvatore Pignataro; Antonino Proto; Erica Menegatti; Angelo Taibi; Paolo Zamboni (Veins and Lymphatics, 2023)
It is well known that the space environment induces major alterations to various human physiological systems, determining a general deconditioning of the body. Medical research programs aim to keep the astronaut’s health status during the mission, enable their ready operation once they arrive at their destination, and allow their safe recovery when returned to Earth. Among the programs coordinated and supported by the Italian Space Agency (ASI), the experiments called Drain Brain, performed by the University of Ferrara, are particularly relevant in this respect. The project, which began with the collaboration of Samantha Cristoforetti in 2014, has demonstrated the capability of a plethysmograph system to study the cerebral circulation and the venous return from the brain to the heart, onboard the International Space Station (ISS). Demonstrating the progressive reduction of the cross-sectional area of the internal jugular vein, particularly significant between pre-flight data collection and the last assessment after 6 months of flight on the ISS (p<0.001). Over the next two years, thanks to the Drain Brain 2.0 project, crews of the International Space Station will be studied with a new version of the plethysmograph, synchronized with the electrocardiogram, to assess cardiac efficiency and brain drainage in relation to symptoms such as blurred vision, numbness, or the feared onset of jugular thrombosis, that is linked to blood flow slowdown due to the absence of the gravitational gradient. Drain Brain 2.0 will also generate important returns to Earth, closing the virtuous circle of terrestrial application of space research.